The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1677/joe.0.1800325
|View full text |Cite
|
Sign up to set email alerts
|

GH prevents apoptosis in cardiomyocytes cultured in vitro through a calcineurin-dependent mechanism

Abstract: The use of GH to treat heart failure has received considerable attention in recent years. Although the mechanisms of its beneficial effects are unknown, it has been implicated in the regulation of apoptosis in several cell types, and cardiomyocyte apoptosis is known to occur in heart failure. We therefore decided to investigate whether GH protects cardiomyocytes from apoptosis. Preliminary experiments confirmed the expression of the GH receptor (GHR) gene in primary cultures of neonatal rat cardiomyocytes (PC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 58 publications
(59 reference statements)
0
5
0
1
Order By: Relevance
“…It is of special interest because it can be triggered physiologically (for the removal of damaged or unwanted cells) and pathologically (foam cells in atherosclerosis) which is regulated by the actions of specific gene products resulting in the removal of damaged or unwanted cells (Squier and Cohen 2001). In our study, nuclear morphology was assessed using a fluorescent dye, DAPI (4′,6-Diamidine-2′-phenylindole dihydrochloride) to assess possible apoptotic changes (Gonzalez-Juanatey et al 2004). Ox-LDL treatment provided visual evidence of nuclear condensation as compared to control cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is of special interest because it can be triggered physiologically (for the removal of damaged or unwanted cells) and pathologically (foam cells in atherosclerosis) which is regulated by the actions of specific gene products resulting in the removal of damaged or unwanted cells (Squier and Cohen 2001). In our study, nuclear morphology was assessed using a fluorescent dye, DAPI (4′,6-Diamidine-2′-phenylindole dihydrochloride) to assess possible apoptotic changes (Gonzalez-Juanatey et al 2004). Ox-LDL treatment provided visual evidence of nuclear condensation as compared to control cells.…”
Section: Resultsmentioning
confidence: 99%
“…This evidence in combination with our findings suggests that IGF-1 can protect against alcohol- induced cardiomyopathy, even in the presence of higher doses of alcohol. Conversely, 1 group was able to show a protective measure of growth hormone in reducing apoptosis in neonatal rat cardiomyocytes; however, they were unable to identify IGF-1 as mediating this effect (Gonzalez-Juanatey et al, 2004). This may be due to the fact that the experiments were performed with neonatal cardiomyocytes which differ in signaling from adult cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that apoptosis is critically linked to the development of heart failure. Growth hormone receptor (GHR) is thought to regulate apoptosis in many cell types including cardiomyocytes through AKT signaling 36 , 37 . In the present study, we found that GHR was significantly downregulated in the heart in MI (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%